EFFECT OF INDUCED MUTATION FOR VARIETAL IMPROVEMENT IN SOME LOCAL GRAPEVINE CULTIVARS - N. Munir; I. Safdar; S. Naz (Journal of Animal and Plant Sciences, 2015)
Grape is important crop with high nutritional value, however there is a great need for improving the quality of the crop. Cultures were maintained in vitro on MS medium supplemented with 2.5 mg/L BAP+ TDZ 3.0 mg/ L. The effect of different doses of gamma irradiation as well as chemical mutagenesis by Sodium azide was studied. It was noted that doses up to 5 Gy helped to increase plant height from irradiated nodes. At 5 Gy, there was an increase of 4.7, 5 and 4.5 cm in plant height in Desi, Sundar Khani and Chinese varieties of grapes respectively. On further increase in concentration from 6 to 10 Gy, there was a gradual decrease in plant height. Sodium azide was selected to induce mutations in the nodal explants. Nodal explants of the varieties were subjected to different sodium azide concentrations ranging from 0.1 to 0.5%. It was noted that the height of plantlet decreased with an increase in concentration of sodium azide In explants treated with 0.2% sodium azide the plant height was 4 cm which increased to 4.2cm when the explants were treated with 0.3% sodium azide.  Further increase in concentration not only caused decreases in length but also led to complete necrosis. In the present study, DNA analysis by RAPD markers was used to analyze mutagenesis. The RAPD analyses indicated that the plantlets subjected to gamma radiation had a great genetic diversity as compared to the control.
Keywords: Grapevine; Induced mutation; varietal improvement